2020
DOI: 10.1590/pboci.2020.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Fluoride Release From Two Different Glass Ionomer Cement and a Novel Alkasite Restorative Material - An in Vitro Study

Abstract: To compare the fluoride release from Conventional Glass Ionomer Cement (GIC), Resin Modified GIC (RMGIC), and Cention N Alkasite Material. Material and Methods: Forty-five disc-shaped specimens of three different restorative materials (Conventional GIC, RMGIC, and Alkasite material) were made and divided into 3 groups (n=15). Fluoride release was evaluated at the end of Day 1, 7, 14, and Day 28 using fluoride ion-selective electrode. Intergroup and Intra-group analysis was done using One-way ANOVA with a Post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
(13 reference statements)
0
12
0
1
Order By: Relevance
“…Alkasite materials contain alkaline fillers that release acid-neutralizing ions. In the mixed form of Cention N, the weight percentage of alkaline glass is around 24.6%, which is responsible for ion release [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alkasite materials contain alkaline fillers that release acid-neutralizing ions. In the mixed form of Cention N, the weight percentage of alkaline glass is around 24.6%, which is responsible for ion release [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various factors such as the fluoride amount present in the cement, powder-liquid ratio, and the capacity for water diffusion in the materials affect fluoride release [17,18]. In this study, the amount of fluoride released from ARM was significantly higher than that from giomer.…”
Section: ⅳ Discussionmentioning
confidence: 53%
“…It could be because light-cured polymerization results in a more tightly bound or less hydrophilic matrix, and a low pH solution induces more rapid degradation of glass filler and ion release when compared to a neutral solution [ 10 , 25 ]. Several studies have shown that CN can release fluoride ions over long periods of time resulting in high fluoride accumulation [ 10 , 25 , 26 , 28 ]. As a result, the amount of fluoride released is likely to be affected by the immersion time.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the amount of fluoride released is likely to be affected by the immersion time. CN has the ability to release fluoride ions, similar to conventional GIC and resin-modified glass-ionomer cement (RMGIC), nevertheless a difference in amount and pattern of fluoride ion release were found in a previous study [ 28 ]. Singh’s study [ 28 ] showed that conventional GIC and RMGIC released the highest fluoride ions in day 1 due to the burst effect, and the fluoride release gradually decreased over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation